Synthesis and acidity characterization of CoAPO-37 - Costa, C. S. (2012)
A well-crystallized sample of CoAPO-37 was prepared. The incorporation of cobalt in the FAU structure framework was indirectly shown by FTIR spectroscopy, which shows peaks assigned to Bronstëd acid sites.